2010
DOI: 10.1007/s10152-010-0212-5
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction, population dynamics and production of Nereis falsa (Nereididae: Polychaeta) on the rocky coast of El Kala National Park, Algeria

Abstract: The polychaete Nereis falsa Quatrefages, 1866 is present in the area of El Kala National Park on the East coast of Algeria. Field investigations were carried out from January to December 2007 to characterize the populations' reproductive cycle, secondary production and dynamics. Reproduction followed the atokous type, and spawning occured from mid-June to the end of August/early September when sea temperature was highest (20-23°C). The diameter of mature oocytes was approximately 180 lm. Mean lifespan was esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…The highest mature oocytes values (168 µm) is about the same as P. dumerilii but is much small than those of P. cultrifera and P. macropus. This result is in agreement with that reported from El-Kala by Daas et al (2010) who showed that during the year 2007 N. falsa reproduces exclusively by atoky from the end of July to early September and that the mean diameter of mature oocyte was approximately 167 µm.…”
Section: Mode Of Reproduction and Reproductive Parameterssupporting
confidence: 83%
“…The highest mature oocytes values (168 µm) is about the same as P. dumerilii but is much small than those of P. cultrifera and P. macropus. This result is in agreement with that reported from El-Kala by Daas et al (2010) who showed that during the year 2007 N. falsa reproduces exclusively by atoky from the end of July to early September and that the mean diameter of mature oocyte was approximately 167 µm.…”
Section: Mode Of Reproduction and Reproductive Parameterssupporting
confidence: 83%
“…Separately, some data was acquired for the waters in the harbour of Algiers (Bakalem & Romano, 1983, 1988Rebzani-Zahaf et al, 1988;Rebzani-Zahaf, 1990, 1992. Populations of some nereids in shallow hard substrates from the eastern part of the Algerian coast were investigated by Rouabah & Scaps (2003) and also by Daas et al (2010). In other work, Younsi et al (2010) recorded the polychaetes of economic interest and Meghlaoui et al (2015a,b) investigated the effects of local pollution on polychaetes.…”
Section: Introductionmentioning
confidence: 99%
“…Ragworm populations from Tubul and Raqui estuaries showed a constant high proportion of juveniles in all seasons, in some cases being higher than 80% in contrast to Lenga, where 'maximum peak' was observed during winter to spring. Size frequency histograms in Lenga and Tubul-Raqui sites showed mainly unimodal cohorts in agreement with other nereid especies, [29][30][31] but different from other related species with plurimodal cohorts. [23,25] Inter-estuary differences were mainly due to more widespread cohorts with higher adult survival in Tubul and Downloaded by [University of Nebraska, Lincoln] at 21:53 09 April 2015 Raqui, and a strong decrease in adult sizes in Lenga.…”
Section: Discussionmentioning
confidence: 90%